Business Strategy to Achieve the Target Time of Loading and Unloading (Laytime) of Coal Commodities - Alfian Indrakusuma; Jhony Warlouw (Journal of Managerial Sciences and Studies, 2026)
This study examines the business strategies a coal mining company in South Kalimantan, Indonesia, can adopt to improve its achievement of the target loading and unloading time (laytime) for coal shipments. The company's reliance on leased jetties, barge transport along the Barito River, and spot contracts has frequently caused loading schedules to shift, resulting in demurrage penalties charged by vessel owners when loading exceeds the agreed laytime. Using purposive sampling, data were collected through interviews with the port, logistics, and business process teams, direct observation of port and logistics operations, and a review of company documents and performance records. Qualitative data were analyzed descriptively, while quantitative data were evaluated using Internal Factor Evaluation, External Factor Evaluation, and SWOT analysis. The results place the company in Cell I of the IE Matrix and Quadrant I of the Grand Strategy Diagram, indicating that its strengths outweigh its weaknesses and its opportunities outweigh its threats. The recommended strategy is therefore an integrative one—specifically backward integration—implemented by acquiring jetties around the coal mines to reduce dependence on leased facilities and accelerate the distribution of stockpiled coal. Demurrage data further show that of 146 shipments incurring demurrage, 60 percent were attributable to jetty-related problems, underscoring jetty ownership as the most critical lever for reducing demurrage costs and achieving the company's laytime targets.